2012
DOI: 10.1016/j.oceaneng.2012.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The interaction factor and directionality in wave energy arrays

Abstract: This paper considers arrays of wave energy devices consisting of oscillating rigid bodies undergoing optimum displacements in regular waves. A previously published identity concerning the directional behaviour of the interaction factor, q, (which characterises an important effect of the array configuration in the context of point absorber theory) is shown to be valid under more general conditions. In fact, this identity is shown to be a consequence of a more fundamental result. Boundary element hydrodynamic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 10 publications
5
49
0
Order By: Relevance
“…Other parameters than the ones discussed here are also relevant for the performance of wave energy parks. Some of these, such as the direction of the incoming wave and the local geometry, were approached in a previous paper [12] and have also been discussed elsewhere, e.g., [7,[29][30][31][32][33]. In this paper, we have restricted the study to include global geometries, number of devices, separating distance between devices, and sea states.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters than the ones discussed here are also relevant for the performance of wave energy parks. Some of these, such as the direction of the incoming wave and the local geometry, were approached in a previous paper [12] and have also been discussed elsewhere, e.g., [7,[29][30][31][32][33]. In this paper, we have restricted the study to include global geometries, number of devices, separating distance between devices, and sea states.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that for OWSCs such as Oyster, the point absorber limit is no longer applicable and hence better and more accurate modelling of the device needs to be undertaken [6]. Some recent investigations also dealt with a detailed analysis of multiple WECs, but most of them did not go beyond three or four of such devices [7][8][9][10]. Indeed, in the literature, there have been very few attempts to understand the dynamics of large finite arrays.…”
Section: Introductionmentioning
confidence: 99%
“…In [30], it was shown that the interaction factor integrated over all incident wave angles equals unity, implying that if there are destructive interaction factors for some incident wave angles, they must be positive for other angles. An underlying assumption for that computation is that the single devices perform at resonance, so that maximum power is absorbed.…”
Section: Discussionmentioning
confidence: 99%